2020
DOI: 10.1177/0896860819887288
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 antitrypsin inhibits formaldehyde-induced apoptosis of human peritoneal mesothelial cells

Abstract: Background: The alpha-1 antitrypsin (AAT) protein has an important role in the anti-inflammatory and apoptotic response. AAT inhibits not only serine proteases but also cysteine and aspartic proteases. Apoptosis results from the sequential activation of cysteine proteases of the caspase family. This study aimed to evaluate the effect of AAT on formaldehyde-induced apoptosis of human peritoneal mesothelial cells (HPMCs). Methods: HPMCs were cultured and treated with formaldehyde (250 µM) to induce apoptosis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…We have focused on the effects of AAT on renal fibrosis, inflammation, and apoptosis. AAT plays an important role not only in protease inhibition, but also in inflammation inhibition and tissue protection [ 13 ]. AAT modulates both the activation and maturation of antigen-presenting cells [ 19 , 20 , 21 ], inhibition of various caspases, and improvement of the mitochondrial membrane stability [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have focused on the effects of AAT on renal fibrosis, inflammation, and apoptosis. AAT plays an important role not only in protease inhibition, but also in inflammation inhibition and tissue protection [ 13 ]. AAT modulates both the activation and maturation of antigen-presenting cells [ 19 , 20 , 21 ], inhibition of various caspases, and improvement of the mitochondrial membrane stability [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…AAT has a broad range of inhibitory functions, including anti-inflammatory properties and, as a result, can limit tissue injury resulting from proteases [ 12 ]. Moreover, AAT protects against apoptosis in various types of cells, such as peritoneal mesenchymal cells, beta cells, and hepatocytes [ 13 , 14 , 15 ]. In particular, it is known that the AAT’s inhibitory function of cysteine proteases of the caspase family, such as caspase-3, plays an important role in preventing apoptosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…GSK3β, a serine/threonine protein kinase, plays a critical role in the regulation of Cyclin D1 expression at both mRNA and protein levels (6). We next evaluated whether AAT overexpression led to enhanced GSK3β expression in iAAT-MSCs compared to iMSCs.…”
Section: Aat-mscs Expressed a Similar Amount Of Gsk3β And β-Catenin C...mentioning
confidence: 99%
“…AAT is a protease inhibitor produced in the liver, protecting the lungs and other organs from neutrophil elastase damage [5]. However, independent of these antiprotease effects, AAT exhibits unique properties such as apoptosis inhibition and promotion of cell proliferation [6,7]. Previous studies have indicated that human AAT-overexpressing mesenchymal stem cells (AAT-MSCs) improve the innate properties of naive MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Peritonitis is a common clinical symptom of GPS infection [4,9,10] and may stem from the impairment of inflammation-induced apoptosis [11]. Meanwhile, numerous studies have shown that the effective treatment of peritonitis is closely related to the regulation of apoptosis [12][13][14]. As reported, apoptosis inhibitor of macrophage ameliorates fungal induced peritonitis injury in mice [14], and short-term regulation of apoptosis may help Molecules 2022, 27, 5083 2 of 10 accelerate recovery after peritonitis and prevent irreversible peritoneal damage [15].…”
Section: Introductionmentioning
confidence: 99%